Later retirement and the labor market re-integration of elderly unemployed workers - Wolfgang Frimmel (Johannes Kepler University of Linz, Department of Economics, 2020)
This paper studies the impact of raising the eligibility age of early retirement on the re-integration into the labor market of elderly unemployed workers. I exploit two Austrian pension reforms increasing the early retirement age step-wise for different quarter-of-birth cohorts. Empirical results based on Austrian administrative data reveal a substantial gender difference in how unemployed workers are affected by the policy change. While unemployed women only benefit little with shorter unemployment duration, modest higher re-employment probability as well as labor income after unemployment, unemployed men benefit in several aspects: although unemployment duration remains unaffected, re-employment chances, labor income and participation in active labor market policies significantly increase. Elderly unemployed workers closer to their early retirement age are systematically assigned to programs increasing their job application and job search skills, while workers more than five years away from their early retirement age are more likely to participate in programs increasing their skills. The gender difference may be explained by the nature of the pension reforms. From a policy perspective, these results suggest that increasing the early retirement age is not only a feasible way to improve the financial sustainability of public pension systems but also improves the re-integration of elderly unemployed male workers.
Keywords: J14; J26; J68; 330; pension reform; early retirement; active labor market policies; nemployment